O lúdico na educação infantil: mediações para uma aprendizagem significativa e prazerosa - NASCIMENTO, Leida Costa Lima do (2023)
The present work, with the theme Playful in Early Childhood Education, aims to study the Importance of Playful in Early Childhood Education for student learning. For this, an investigation was carried out on the subject in question, because, as Knebel (2014, p. 278) mentions, ludic activity is an action expressed through games and games. The act of playing can be carried out independently of time, space or objects and this allows the child to create, recreate, invent and use their imagination, making the school space attractive. Thus, from the problem raised, the general objective was delimited. It is a bibliographical study that seeks to analyze and present a synthesis on how different authors analyze this important relationship between play and the learning process in early childhood education. In addition to authors, we resorted to the critical analysis of official documents that deal with this subject, such as: LDB, PCNS, BNCC and curricular references. In this study, it was possible to analyze the importance of activities, consisting of games and games, as they help in the development and autonomy of the child.